The Nymph of Holcoperla angularis (Wisely) (Plecoptera: Gripopterygidae) from New Zealand - McLellan, Ian (Illiesia, 2006)
The nymph of Holcoperla angularis (Wisely) is described and figured for the first time. Notes on habitat and a distribution map are given.
Keywords: insekti; Plecoptera; vrbnice; Nova Zelandija